40 days and 40 nights : Darwin, intelligent design, God, Oxycontin, and other oddities on trial in Pennsylvania - Chapman, Matthew, 1950- (New York, NY : Collins, 2007)
In this story of evolution, religion, politics, and personalities, writer Chapman captures the story behind the headlines in the debate over God and science in America. In Kitzmiller v. Dover Board of Education, decided in late 2005, a Republican judge rendered a surprising verdict in a case that pitted the teaching of intelligent design against the teaching of evolution. Taking place in a small Pennsylvania school district, the case had national repercussions. Chapman, the great-great-grandson of Charles Darwin, covered the trial from beginning to end. Through his encounters with the participants--creationists, preachers, teachers, scientists on both sides of the issue, lawyers, theologians, the judge, and the parents who resisted the fundamentalist proponents of intelligent design--Chapman tells a story of ordinary people doing battle in America over the place of religion and science in modern life.--From publisher description.
pt. 1. In the beginning. Genesis -- Early days -- Bill and Alan -- Life on board -- Miller grinds it up -- Other primates -- The teachers' story -- The audible ping -- A libertarian Buddhist girl scout leader -- Pennock qua Pennock, Finches qua Finches -- Summertime -- Marilyn Monroe is alive and well and living in Dover -- John Haught and the teapot of wisdom -- The panda cometh -- The smoking gun -- Barbara Forrest and the panda's tale -- When you open your eyes in hell -- Kevin fills the gaps -- You pay your nickel and you go for a ride -- pt. 2. The New Testament of science. The man from Bethlehem -- Moral decay -- Sudden disappearance, sudden emergence -- Buckingham -- The reporters -- Bonsell and his trinity of loyal women -- The two Scotts -- The genie is out of the bottle -- Revelation.
Keywords: Kitzmiller, Tammy -- Trials, litigation, etc; Scopes, John Thomas -- Trials, litigation, etc; Dover Area School District (Dover, Pa.) -- Trials, litigation, etc; Trials -- Pennsylvania -- Dover; Evolution (Biology) -- Study and teaching -- Law and legislation -- Pennsylvania -- Dover; Trial and arbitral proceedings